Kinematic analysis of the landing phase in ski jumping - Greimel, F.; Virmavirta, M.; Schwameder, H. (Science and Skiing IV, 2008)
INTRODUCTION: Although the landing and its preparation are important in ski jumping with respect to performance and safety, the number of scientific investigations of these phases is fairly small (Schwameder, 2008). Along with the jump length the scores given by the judges for the technical performance of the jump in general and the landing phase in particular are the key factors determining the performance in ski jumping. The purposes of this study were to present a kinematic description of the landing phase and to detect kinematic variables related to performance.